2013 IEEE 10th International Symposium on Biomedical Imaging 2013
DOI: 10.1109/isbi.2013.6556434
|View full text |Cite
|
Sign up to set email alerts
|

FEM-based automatic segmentation of muscle and fat tissues from thoracic CT images

Abstract: The estimation of body composition (i.e., proportions of muscle and fat tissues) in cancer patients has important clinical and research applications. In particular, chemotherapy drug dosage is determined after taking into account the muscle and fat proportions in the patient's body. Recently, there has been considerable interest in studying the correlation between survival and body composition in cancer patients. We propose a fully automated framework for segmentation and quantification of muscle and fat tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Further, our proposed segmentation framework handles both abdominal and thoracic CT images in a unified manner via the shape modeling approach. This paper is an extended version of our previous works [29], [30].…”
Section: B Our Contributionsmentioning
confidence: 92%
“…Further, our proposed segmentation framework handles both abdominal and thoracic CT images in a unified manner via the shape modeling approach. This paper is an extended version of our previous works [29], [30].…”
Section: B Our Contributionsmentioning
confidence: 92%
“…Here, we address this problem and propose another approach to localize the L3 slice. Initial papers on automatic L3 CT segmentation proposed shape prior models for body composition analysis at L3 and at T4 vertebra levels (Chung et al, 2009;Popuri et al, 2013Popuri et al, , 2016. Recently, deep learning methods have been used for L3 tissue segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle segmentation in L3 (Chung et al, 2009;Popuri et al, 2016) and in T4 (Popuri et al, 2013) using a shape prior modeling approach has been previously reported. Kamiya et al addressed the segmentation of individual muscle groups such as psoas major and rectus abdominis muscles from CT images by generating muscle group specific shape models (Kamiya et al, 2009;Kamiya et al, 2012).…”
Section: Introductionmentioning
confidence: 99%